Evaluation of hospital’s obedience in medical solid waste management - Yuni Lisafitri; Merza Rahmawati; Rizka Firdausi Pertiwi; Bambang Prasetio (Penerbit Kemala Indonesia, 2017)
Waste is an environmental issue that quite unsettling right now. Hospitals are health facilities for community but also become one of waste contributor. Waste from hospital activities was called medical waste. Medical waste can be a source of disease for humans and other living organism and can disrupt environmental stability if not managed properly. The management of medical waste must be appropriate with regulations, but there are still many health facilities that have not managed according to the regulations. This study was conducted to evaluate of medical waste management in hospital to government regulation No. 101/2014 and Regulation of environment and forestry minister No. 56/2015. The research was conducted through several step from literature study to direct survey in the field through interviews and observations of the medical waste management. That information is evaluated in accordance with the waste management that has been regulated in government regulation No. 101/2014 and regulation of environment and forestry minister No. 56/2015. There are seven activities in the management of hazardous and toxic waste but this hospital only carry out two steps, such as collection and storage activities. Some of their doing in collection and storage activities was still not accordance with the regulations.